Inpatient Weight Restoration Treatment Is Associated with Decrease in Post-Meal Anxiety - Magnus Sjögren (MDPI AG, 2021)
Objective: Anorexia nervosa (AN) is characterized by weight loss, distorted body image with fear of becoming fat and associated with anxiety, especially in relation to food intake. Anxiety in relation to meals and weight restoration remains a major challenge in the treatment of AN. We examined the effects of inpatient weight restoration treatment on levels of post-meal anxiety using visual analogue scale (VAS) ratings in patients with AN. Materials: Thirty-two patients with AN, all part of the PROspective Longitudinal all-comer inclusion study on Eating Disorders (PROLED) were followed over eight weeks with baseline psychometric measures and weekly VAS anxiety self-scoring. Methods: Apart from the weekly body mass index (BMI) and VAS, patients were characterized at baseline using the Eating Disorder Examination Questionnaire (EDE-Q), Eating Disorder Inventory (EDI), Symptom Check List 92 (SCL-92), Major Depression Inventory (MDI), and Autism Quotient (AQ). Results: The results showed a significant time effect, Wilks Lambda = 0.523, F = 3.12, p < 0.05 (power of 0.862), indicating a reduction in VAS scores of anxiety from baseline to week 8. There was no effect of baseline medication or scores of MDI on the results. BMI increased from a mean of 15.16 (week 1) to 17.35 (week 8). In comparison, patients dropping out after only three weeks (n = 31) also had a trend toward a reduction in VAS anxiety (ns). Conclusions: Inpatient weight restoration treatment is associated with a decrease in post-meal anxiety in AN, an effect that occurs early and becomes clinically significant in patients who stay in treatment.